ANALISIS KEMACETAN LALU LINTAS RUAS JALAN KYAI AMIR KOTA SURABAYA - Nursasli, Muhammad; Hamzah, Yayu Sriwahyuni (Universitas Teuku Umar, 2023)
Kyai Amir Road is located in Manukan Kulon sub-district, Tandes District, Surabaya City. This road often experiences traffic congestion which are very disturbing for residents. The aim of this research is to find out how much capacity the Kyai Amir road section can accommodate, what the level of vehicle volume on the Kyai Amir road section is, how much the degree of saturation is, and what the service level value of the Kyai Amir road is. This research method was carried out using a real time survey at a predetermined time and the results of observations in the field. The results of the research can show that the capacity that can be accommodated by the Kyai Amir road section for a 2 lane 2 direction undivided road is 1,385 pcu/hour. The highest volume level was obtained on Monday at 17.00 - 18.00 at 1,359.9 pcu/hour. The highest degree of saturation of the Kyai Amir road section is 0.98 and can be obtained from the classification of service level values as E (0.90 – 1.00) which can be interpreted as unstable flow, low speed, dense volume or approaching capacity.